The Future Value: Building An Excellent Generation Through Investment, Technology, And Multimedia With An Impactful Campus - Muhammad Fikry Januar; Sekar Fauzia Larasati; Solihin; Imma Ismaniar; Dede Ibrahim Maulana; Rizki Idham Sofyan (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2026)
The Future Value is a community service activity (Pengabdian kepada Masyarakat/PKM) organized by Politeknik Mardira Indonesia on December 31, 2025, held at the university's main auditorium in Majalengka Regency, West Java. The activity was conducted in a workshop format, focused on cryptocurrency as an emerging digital investment asset that is increasingly relevant yet still poorly understood by the general public, particularly among youth. Two expert speakers delivered materials covering two interconnected themes: an introduction to cryptocurrency and blockchain technology, and investment strategies, risks, regulations, and ethics in the crypto asset market. A total of 85 participants attended, comprising high school and vocational students, fresh graduates, and young entrepreneurs. Through interactive discussions, question-and-answer sessions, and direct engagement with practitioners, participants gained foundational knowledge of the crypto ecosystem and a more balanced understanding of its opportunities and risks. Participant evaluation showed that over 82% felt their understanding of cryptocurrency significantly increased, and more than 75% expressed greater confidence in assessing crypto investment decisions after attending the workshop. This activity reflects the kampus berdampak (impactful campus) spirit of Politeknik Mardira Indonesia, affirming the institution's commitment to delivering relevant, practical, and accessible knowledge to the community.